Lateral Habenula Glutamatergic Neurons Modulate Isoflurane Anesthesia in Mice - Liu, Chengxi; Liu, Junxiao; Zhou, Liang; He, Haifeng; Zhang, Yu; Cai, Shuang; Yuan, Chengdong; Luo, Tianyuan; Zheng, Jijian; Yu, Tian; Zhang, Mazhong (Frontiers in Molecular Neuroscience, 2021)
Since their introduction in the 1840s, one of the largest mysteries of modern anaesthesia are how general anesthetics create the state of reversible loss of consciousness. Increasing researchers have shown that neural pathways that regulate endogenous sleep–wake systems are also involved in general anaesthesia. Recently, the Lateral Habenula (LHb) was considered as a hot spot for both natural sleep-wake and propofol-induced sedation; however, the role of the LHb and related pathways in the isoflurane-induced unconsciousness has yet to be identified. Here, using real-time calcium fiber photometry recordings in vivo, we found that isoflurane reversibly increased the activity of LHb glutamatergic neurons. Then, we selectively ablated LHb glutamatergic neurons in Vglut2-cre mice, which caused a longer induction time and less recovery time along with a decrease in delta-band power in mice under isoflurane anaesthesia. Furthermore, using a chemogenetic approach to specifically activate LHb glutamatergic neurons shortened the induction time and prolonged the recovery time in mice under isoflurane anaesthesia with an increase in delta-band power. In contrast, special inhibition of LHb glutamatergic neurons was very similar to the effects of selective lesions of LHb glutamatergic neurons. Finally, optogenetic activation of LHb glutamatergic neurons or the synaptic terminals of LHb glutamatergic neurons in the rostromedial tegmental nucleus (RMTg) produced a hypnosis-promoting effect in isoflurane anaesthesia with an increase in slow wave activity. Our results suggest that LHb glutamatergic neurons and pathway are vital in modulating isoflurane anaesthesia.